JARINGAN SOSIAL DALAM PEMBENTUKAN PERILAKU SISWA MEROKOK - Nawaar Faizatun Ashri; Nurhadi Nurhadi; Okta Hadi Nurcahyono (Faculty of Social Science, Universitas Negeri Padang, 2020)
The purpose of this research was to know the social networks of smoking behavior of active smoker students, especially in high school of Surakarta. This study aimed to describe agents that contribute to form this behavior through social ties based on Marwell theory of Social Networks. The methods that used in this study was descriptive qualitative with ethnography approach. The data was collected through interview using WhatsApp application. The data was analyzed with theory of Social Network from Marwell and compared to related researches. Informants in this study were ten high school students in Surakarta who active in smoking behavior. The results of this study indicated that its habit started from curiosity and imitation of others into an action that receive “support” from people around. It could be concluded that student's decision of smoking was determined by their relationship with the social milieu which was also an active smoker, such as family and peer groups.